A Survey on Position‐Based Simulation Methods in Computer Graphics. (1st May 2014) - Bender, Jan; Müller, Matthias; Otaduy, Miguel A.; Teschner, Matthias; Macklin, Miles
<x xml:space="preserve">Abstract</x> The dynamic simulation of mechanical effects has a long history in computer graphics. The classical methods in this field discretize Newton's second law in a variety of Lagrangian or Eulerian ways, and formulate forces appropriate for each mechanical effect: joints for rigid bodies; stretching, shearing, or bending for deformable bodies; and pressure, or viscosity for fluids, to mention just a few. In the last years the class of position‐based methods has become popular in the graphics community. These kinds of methods are fast, stable and controllable which make them well‐suited for use in interactive environments. Position‐based methods are not as accurate as force‐based methods in general but they provide visual plausibility. This state‐of‐the‐art report covers the large variety of position‐based methods that were developed in the field of physically based simulation. This state‐of‐the‐art report covers the large variety of position‐based methods that were developed in the field of physically based simulation. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>